Gender and cooperation in children: Experiments in Colombia and Sweden - Juan-Camilo Cárdenas; Anna Dreber; Emma von Essen; Eva Ranehill (Stockholm School of Economics, The Economic Research Institute (EFI), 2011)
We compare how children aged 9-12 in Colombia and Sweden cooperate in a Prisoner's Dilemma. We introduce a new measurement device for cooperation that can be easily understood by children. There is some evidence of more cooperation in Sweden than in Colombia. Girls in Colombia are less cooperative than boys, whereas our results indicate the opposite in Sweden. Girls are in general more cooperative with boys than with girls. Relating cooperation to competitiveness, this appears to be task and country dependent.
Keywords: C91; D03; J16; 330; cooperation; children; gender differences; experiment; Gefangenendilemma; Kooperation; Geschlecht; Test; Kolumbien; Schweden